SKETCH'NDO: A framework for the creation of task-based serious games. (June 2016) - Moya, Sergio; Tost, Dani; Grau, Sergi; Barnekow, Ariel von; Felix, Eloy
Abstract: We present SKETCH'NDO, a framework for the interactive design and creation of single-user task-based serious games in 3D virtual environments. The games are dimensionally congruent: inherently 2D tasks such as reading and writing are done in 2D, while manipulation tasks are 3D. The architecture of the system allows educators to design the tasks with a graphical editor that creates the game automatically. This editor does not require gaming expertise. It only needs educators to specify the correct ways of doing the task, without having to consider all possible erroneous learner's decisions. SKETCH'NDO provides a complete mechanism of monitoring and evaluation of the learner's performance that allows a precise assessment of the learning process. It offers a gradation of levels of assistance that can be fixed by educators or automatically adjusted to the trainee's skills. This way, the same task can be trained from a strictly conductist strategy to a fully constructivist one. Abstract : Graphical abstract: Abstract : Highlights: An authoring system for the creation of Serious Games (SG) for professional training. A SG editor usable by domain experts without knowledge of game technology. A concise specification of the tasks expressing correct ways of doing them. A continuous evaluation of the player's behaviour based on diverse indicators. Dimensionally congruent graphics integrating in a natural way 2D and 3D actions.